Abu Theirah, Nasiriyah (Southern Iraq): Preliminary report on the 2013 excavation campaign - D'Agostino, Franco; Romano, Licia; Kadhem Ghanim, Ali (ISIMU, 2016)
In this paper the results of the third excavation campaign in Fall 2013 at Abu Tbeirah, Nasiriyah (Southern Iraq), a site whose remains can be chronologically ascribed so far to the second half of 3rd Millennium BC, are presented. The archeological activities in the South-Eastern and North-Eastern sectors of the tell are shown, with the aim of shedding a new light on the life of a big Sumerian city located only 16 km East from the great ancient site of Ur.